1992
DOI: 10.1007/bf00201948
|View full text |Cite
|
Sign up to set email alerts
|

Phytotropin-binding sites and auxin transport in Cucurbita pepo: evidence for two recognition sites

Abstract: Two properties of phytotropins, their ability to bind to 1-N-naphthylphthalamic acid (NPA) receptors located on microsomal vesicles isolated from Cucurbita pepo L. hypocotyls, and to stimulate auxin (indol-3-yl acetic acid, IAA) accumulation into such vesicles by blocking its efflux from them, were assessed in double labelling experiments using [2,3,4,5-(3)H]1-N-naphthylphthalamic acid and 3-indolyl-[2-(14)C]acetic acid. Two sites of differing affinities and activities on IAA accumulation were found. 1-N-Napht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…At low micromolar concentrations, auxin transport inhibitors are thought to impair directly the activity of auxin transporters [37,41,101], whereas at higher concentrations (>50 M) auxin transport inhibitors seem to interfere with the bundling status of the actin cytoskeleton, thus affecting the presence of auxin exporters on the plasma membrane in this manner [7,[102][103][104][105]. These two modes of actions for NPA on auxin transport, which could be even interconnected [7], might be represented by two distinct NPA binding affinities, as reported for zucchini plasma membrane and speculated to correspond to the auxin transporter itself and an additional NPA-binding regulatory subunit [106]. While the number of NPA binding sites in the plant cell is currently highly debated [107], there is general agreement that NPA binding is peripheral to the plasma membrane and associated with the actin cytoskeleton [108][109][110].…”
Section: Imunophilins Might Mediate Auxin Transporter Sensitivity To Npamentioning
confidence: 75%
See 1 more Smart Citation
“…At low micromolar concentrations, auxin transport inhibitors are thought to impair directly the activity of auxin transporters [37,41,101], whereas at higher concentrations (>50 M) auxin transport inhibitors seem to interfere with the bundling status of the actin cytoskeleton, thus affecting the presence of auxin exporters on the plasma membrane in this manner [7,[102][103][104][105]. These two modes of actions for NPA on auxin transport, which could be even interconnected [7], might be represented by two distinct NPA binding affinities, as reported for zucchini plasma membrane and speculated to correspond to the auxin transporter itself and an additional NPA-binding regulatory subunit [106]. While the number of NPA binding sites in the plant cell is currently highly debated [107], there is general agreement that NPA binding is peripheral to the plasma membrane and associated with the actin cytoskeleton [108][109][110].…”
Section: Imunophilins Might Mediate Auxin Transporter Sensitivity To Npamentioning
confidence: 75%
“…One could speculate, that independent interactions of NPA with both ABCBs and PINs could in fact account for the two NPA-binding affinities found in zucchini plasma membrane [106]. However, conclusive data are lacking demonstrating NPA binding or direct inhibition of PIN transport proteins in auxin-transport systems [37,39,41].…”
Section: Imunophilins Might Mediate Auxin Transporter Sensitivity To Npamentioning
confidence: 99%
“…However, Thomson et al [28] have suggested that TIBA was transported basipetally in corn coleoptiles. TIBA has been reported to compete for the same binding sites as that of IAA [28][29][30]. In addition, TIBA is transported in a polar basipetal manner, but NPA is not [28].…”
Section: Discussionmentioning
confidence: 99%
“…We narrowed our focus to this compound 10824, subsequently named BUM, 5 verifying consistently growth inhibition under a variety of assay conditions in follow-up screenings. The fact that BUM/10824 produced pin-formed inflorescences in analogy to the well established ATI, NPA (15,16,37), and that both contain a 2-(formyl)-benzoic acid core (Fig. 1B), prompted us to compare growth defects between BUM and NPA over a wide concentration range.…”
Section: A Chemical Library Screen For Growth and Developmentalmentioning
confidence: 99%
“…Until today, the identity, number, and affinity of putative NPA-bind-ing proteins (NBPs) is still controversial (13)(14)(15)(16)(17). However, the current consensus is that the auxin efflux complex consists of at least two proteins: a membrane-integral transporter and an NBP-regulatory subunit (13)(14)(15)18). Several lines of evidence suggest that PIN proteins do not themselves act as NBPs (19), although NPA application results in a pin-formed inflorescence, mimicking PIN1 loss of function (20).…”
mentioning
confidence: 99%